Knowledge, Attitudes and Practices Regarding the Screening of Colorectal Cancer among Primary Care Physicians in Baghdad During 2022 - M. Abbas, Mais; A. Alkhazrajy, Lujain (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Colorectal cancer (CRC) is the third most common cancer in the world and the fourth leading cause of death. In Iraq, it is primarily a disease of old age, but its incidence and mortality rates are increasing across all age groups. To address this concerning trend, it is crucial to raise public awareness, implement screening programs, and develop effective management strategies. Objectives: To evaluate primary care physician’s knowledge, attitude, and practice regarding early screening for colorectal cancer. Methods: A cross-sectional study was carried out in Baghdad, from the 1st of June 2022 to the 1st of January 2023. The study involved 400 physicians who provided primary health care services. Data were collected through direct interviews using a self-structured questionnaire. The association between variables was explored using the Chi-square test, with a P value of less than 0.05 considered statistically significant. Results: The study involved physicians with a mean age of 38.0±7.62 years. Of the participants, 27.3% (109) were males and 72.8% (291) were females. The study found that 268 (67.0%) participants had good knowledge, 178 (44.5%) had a positive attitude, and 122 (30.5%) participants had good practice. Those aged 36-45 years, with less than 10 years of employment experience, and family medicine residents had significantly higher levels of good knowledge (P < 0.05). Females had a significantly more positive attitude (P=0.001). Conclusions: It was observed that participants had good knowledge about the CRC screening program. However, they showed poor attitude and practice towards it. The age group of 36-45 years, individuals with less than 10 years of employment, and family physicians had better knowledge than others. Among the family medicine female residents, a positive attitude was observed